Association of BET1L and TNRC6B with uterine leiomyoma risk and its relevant clinical features in Han Chinese population - Bailing Liu (Nature Portfolio, 2018)
Abstract Previous studies have shown that uterine leiomyomas (UL) are benign tumours with contributions from environmental and genetic factors. We aimed to replicate two initial significant genetic factors, TNRC6B and BET1L, in a Han Chinese population. A total of 2,055 study subjects were recruited, and 55 SNPs mapped to TNRC6B and BET1L were selected and genotyped in samples from these subjects. Genetic associations were analysed at both the single marker and haplotype levels. Associations between targeted SNPs and relevant clinical features of UL were analysed in case only samples. Functional consequences of significant SNPs were analysed by bioinformatics tools. Two SNPs, rs2280543 from BET1L (χ2 = 18.3, OR = 0.64, P = 1.87 × 10−5) and rs12484776 from TNRC6B (χ2 = 19.7, OR = 1.40, P = 8.91 × 10−6), were identified as significantly associated with the disease status of UL. Rs2280543 was significantly associated with the number of fibroid nodes (P = 0.0007), while rs12484776 was significantly associated with node size (χ2 = 54.88, P = 3.44 × 10−11). Both SNPs were a significant eQTL for their genes. In this study, we have shown that both BET1L and TNRC6B contributed to the risk of UL in Chinese women. Significant SNPs from BET1L and TNRC6B were also identified as significantly associated with the number of fibroid nodes and the size of the node, respectively.